Solar Energy Potential in Pakistan: A Review - Aqsa Muhammadi; Muhammad Wasib; Salman Muhammadi; Samreen Riaz Ahmed; Altaf Hussain Lahori; Sergij Vambol; Oleksandr Trush (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
This review paper focuses on the potential of solar energy and its applications in addressing the energy crisis in Pakistan. Currently heavily reliant on non-renewable sources, Pakistan faces severe power shortages and lacks access to electricity in many rural areas. The paper highlighting its geographical position and the availability of solar radiation. The review emphasizes the need to harness the vast solar energy resources available in the country. It was discovered that over 100,000 MW of electricity from sunlight could be generated, particularly in regions within the Sunny Belt. The annual average daily global radiation of Pakistan is: horizontal (GHI) - 16 MJ/m2, oblique (GTI) - 13 MJ/m2. The minimum annual average daily GHI in Pakistan is higher than the world average annual average daily GHI. At the same time, in Pakistan, thermal power generation accounts for most of the energy production (61% in 2020, 63% in 2021, and 61% in 2022), while renewable energy sources account for the least (3% in 2020, 2% in 2021, and 3% in 2022). It emphasizes the need for research and development, as well as policy support, to promote the adoption of solar energy technologies. In conclusion, this review paper sheds light on the significance of solar thermal energy as a renewable and sustainable solution for Pakistan's energy dilemma. It underscores the need for increased investments, technological advancements, and policy interventions to harness the immense solar energy potential and pave the way for a greener and more energy-secure future in Pakistan.